Text on back: 'Feierliche Enthüllung einer Büste von Friedrich König, dem Erfinder der Schnellpresse. ...'
Text on back: 'Feierliche Enthüllung einer Büste von Friedrich König, dem Erfinder der Schnellpresse. ...'.